Some anthropologic characteristics of elite female handball players at different playing positions - Rogulj, N.; Srhoj, V.; Nazor, M.; Srhoj, L.; Cavala, M. (Collegium Antropologicum, 2005)
Differences in motor and psychologic variables according to playing positions were analyzed in a sample of 53 elite female handball players, members of junior and senior national team. Motor status included 8 variables for assessment of explosive strength of landing and throwing, agility, speed strength, movement frequency, and flexibility. Psychologic status was analyzed through 4 dimensions according to Eysenck: extroversion, psychotic behavior, neurotic behavior, and lie. The anthropologic features analyzed showed statistically significant differences. Considering motor abilities, differences were recorded in the variables for assessment of speed strength, agility and leg movement frequency, where wings predominated, whereas goalkeepers showed predominance in flexibility. In psychologic status, differeces were present in the variable for assessment of extroversion, which was most pronounced in wings, whereas psychotic behavior was more expressed in those at pivot position. The differences were primarily consequential to the selection of players of a specific anthropologic profile for particular playing positions. The hypothesis of the impact of kinesiologic specificities of a particular playing position on the formation of the players' anthropologic profile should be scientifically tested. Study results may found application in training and contest practice, especially in forming anthropologic models for particular positions during the process of player selection.